First documented record of Leucopternis melanops (Latham, 1790) (Aves: Accipitridae) in the state of Maranhão and update of the geographic distribution of this species in Brazil - Pinheiro, Leonardo Victor Soares; Cerqueira, Pablo Vieira; Leite, Gabriel Augusto; Fialho, Marcos de Souza; Gonsioroski, Gustavo (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2021)
The Black-faced hawk, Leucopternis melanops (Latham, 1790), is the representative of the genus with the greatest geographic distribution, being common on the northern bank of the Amazon River and with rare records on the southern bank (Acre, Amazonas, Mato Grosso, Pará and Rondônia). On June 24, 2018, an individual of L. melanops was found in the municipality of Centro Novo do Maranhão, state of Maranhão, Brazil, within the limits of the Gurupi Biological Reserve, which is the first documented record for the state. This record, added to others, served to update the limits of the distribution of L. melanops in Brazil, in addition to highlighting the importance of the Gurupi mosaic in maintaining unusual species.
Keywords: Biological Reserve of Gurupi; Conservation units; Belém area of endemism; Distribution range limits